Digital Enjoyment or Social Disconnection : How Do Online Games Affect Students' Social Lives? - Chrisanta Kezia Yemima; Diana Septi Purnama (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2024)
This research aims to analyze the relationship between online game addiction and social interaction and its implications for students' enthusiasm for learning. This research used a quantitative approach with a survey method involving 100 Surakarta students selected through purposive sampling. The instrument used to measure Social Interaction was adapted from  (2024) with a reliability coefficient (alpha) of 0.915. And the Online Game Addiction Scale, adapted fromArua et al., (2023) with a reliability coefficient (alpha) of 0.853. Data analysis used descriptive statistics, assumption tests, Pearson correlation, t-test, and coefficient of determination. The results showed that the majority of respondents had a moderate level of online gaming addiction, with a significant negative correlation between gaming addiction and social interaction. Addiction rates were higher in men than women. Interventions should target social and individual contexts, combining education and social support to reduce online gaming addiction among students. Students addicted to online games tend to spend more time in the virtual world; this can divert students' enthusiasm from learning activities. Students become less focused, get tired quickly, or lose enthusiasm for learning because more time and energy is devoted to playing games.